Determination of Magnitudes and Orientation of the Paleostress of Bekhme Structure in Shaqlawa area, Northerneastern Iraq - AL- Hachem, Atheer E. K.; Hassan, Shatha (Iraqi Journal of Science, 2021)
This study presents the determination of the paleostress magnitudes and orientation of Bekhme Structure in Shaqlawa area, northeastern Iraq. Paleostress analysis of slip-fault measurements is performed using Right dihedral, Lisle diagram, and Mohr Circles methods. Depending on Mohr Circles, Bott law, and vertical thickness, the magnitudes of the paleostress at the time of the tectonic activity were determined. Firstly, Georient Software was used to estimate the orientation of the paleostresses (σ1, σ2, and σ3). Secondly, using the rupture –friction law, taking into account the depth of the overburden and the vertical stress (σv),the magnitudes of the paleostresses were calculated (σ1=4500 bars, σ2=1900 bars and σ3=700 bars). The high magnitudes of the principal stress axes may be attributed to the active tectonic events which led to the deformation of the area during the Cretaceous and Tertiary periods. The study area shows that the poles of the measured faults lie in the reactivated area of Mohr circles. This indicates the instability of the study area. The study area is estimated to have high importance, due to the possibility of the existence of deposited hydrocarbons. Fold- Thrust belt marks the deformation fronts of the major orogeny that forms from the collision of the Arabian Plate with the Turkish and Iranian Plates.